Guava based intercropping for doubling farmers’ income - Kumar Yadav, Rakesh; Jain, M C; Yadav, V K; Yadav, R K (Indian Horticulture, 2022)
Sh. Ghanshyam regularly observe the prices online and accordingly sells his produce in cities like, Kota, Jaipur, own farm etc. and elsewhere from where he gets more return. He uses social media actively on regular basis for promotion of produce like, farm/orchard photographs, harvested produce, etc. He also adopted animal husbandry and properly utilises the by-products obtained from the crops. Sh. Ghanshyam is popular among the farmers community in his block for adopting new technologies and his success stories are published periodically in magazines and newspapers. Being inspired by Mr. Ghanshyam, nearby farmers of his village and other villages are adopting new technologies and knowledge provided by Agriculture University, Kota. He also inspires the farmers by providing training at his own farm for adopting new interventions. Scientists of Agriculture University, Kota also visit his field as and when he call them to solve his problems.